Effect of cardiosphere-derived cells on segmental myocardial function after myocardial infarction: ALLSTAR randomised clinical trial. Issue 2 (7th July 2021) - Ostovaneh, Mohammad R; Makkar, Raj R; Ambale-Venkatesh, Bharath; Ascheim, Deborah; Chakravarty, Tarun; Henry, Timothy D; Kowalchuk, Glen; Aguirre, Frank V; Kereiakes, Dean J; Povsic, Thomas J; Schatz, Richard; Traverse, Jay H; et al.
Abstract : Background: Most cell therapy trials failed to show an improvement in global left ventricular (LV) function measures after myocardial infarction (MI). Myocardial segments are heterogeneously impacted by MI. Global LV function indices are not able to detect the small treatment effects on segmental myocardial function which may have prognostic implications for cardiac events. We aimed to test the efficacy of allogeneic cardiosphere-derived cells (CDCs) for improving regional myocardial function and contractility. Methods: In this exploratory analysis of a randomised clinical trial, 142 patients with post-MI with LVEF <45% and 15% or greater LV scar size were randomised in 2:1 ratio to receive intracoronary infusion of allogenic CDCs or placebo, respectively. Change in segmental myocardial circumferential strain (Ecc) by MRI from baseline to 6 months was compared between CDCs and placebo groups. Results: In total, 124 patients completed the 6-month follow-up (mean (SD) age 54.3 (10.8) and 108 (87.1%) men). Segmental Ecc improvement was significantly greater in patients receiving CDC (−0.5% (4.0)) compared with placebo (0.2% (3.7), p=0.05). The greatest benefit for improvement in segmental Ecc was observed in segments containing scar tissue (change in segmental Ecc of −0.7% (3.5) in patients receiving CDC vs 0.04% (3.7) in the placebo group, p=0.04). Conclusions: In patients with post-MI LV dysfunction, CDC administration resulted in improved segmental myocardial function. Our findings highlight the importance of segmental myocardial function indices as an endpoint in future clinical trials of patients with post-MI. Trial registration number: NCT01458405 .